Comparative genetic analysis of blood and semen samples in sperm donors from Hunan, China - Chuan Huang; Li-Ming Chu; Bo Liang; Hui-Lan Wu; Bai-Shun Li; Shuai Ren; Mei-Ling Hou; Hong-Chuan Nie; Ling-Yin Kong; Li-Qing Fan; Juan Du; Wen-Bing Zhu (Annals of Medicine)
Objectives At present, most genetic tests or carrier screening are performed with blood samples, and the known carrier rate of disease-causing variants is also derived from blood. For semen donors, what is really passed on to offspring is the pathogenic variant in their sperm. This study aimed to determine whether pathogenic variants identified in the sperm of young semen donors are also present in their blood, and whether matching results for blood are consistent with results for sperm.Methods We included 40 paired sperm and blood samples from 40 qualified semen donors at the Hunan Province Human Sperm Bank of China. All samples underwent exome sequencing (ES) analysis, and the pathogenicity was assessed according to the American College of Medical Genetics (ACMG) guidelines. Scoring for sperm donation matching, which was based on gene scoring and variant scoring, was also used to assess the consistency of sperm and blood genetic test results.Results A total of 108 pathogenic (P)/likely pathogenic (LP) variants in 82 genes were identified. The highest carrier had 7 variants, and there was also one donor did not carry any P/LP variant. On average, each donor carried 2.7 P/LP variants. Among all the P/LP variants, missense mutation was the dominant type and most of them were located in exonic regions. Chromosome 1 harboured the largest number of variants and no pathogenic copy number variants (CNV) was identified in semen donors. The P/LP variant of all the 40 semen donors was consistent by comparing sperm and blood. Except for one case that was slightly different, the rest simulated matching results for blood were all consistent with results for sperm.Conclusions It is reasonable to choose either blood or sperm for genetic screening in semen donors.